IMPLEMENTASI PUNISHMENT DALAM MENINGKATKAN AKHLAK MAHMUDAH SISWA KELAS IV SDN 15 KARTIASA TAHUN AJARAN 2023-2024 - Lini Umayrah; Suhari, Mauizatul Hasanah (ADISAM PUBLISHER, 2025)
This study aims to describe the implementation of punishment in improving the good morals of fourth-grade students at SDN 15 Kartiasa and to obtain information about the planning, execution, and evaluation of punishment in enhancing the good morals of these students.This research employs a qualitative approach and is of a phenomenological type. Data collection techniques include observation, interviews, and documentation. The data analysis techniques used in this study are data reduction, data display, and conclusion drawing. To verify the validity of the research data, the technique employed is member-check triangulation.The results of the study indicate that: The planning of punishment to improve the good morals of fourth-grade students at SDN 15 Kartiasa involves: (1) Choosing punishments appropriate to the level of violation, student characteristics, and the situation, (2) Ensuring that punishments have educational objectives to encourage positive future behavior by identifying those goals, (3) Explaining the consequences that will occur if students make mistakes/violations before imposing punishment, and involving students in discussions, (4) Applying punishments consistently and fairly, without regard to who committed the violation, (5) Determining the evaluation of punishment, including setting objectives, assessing behavioral changes, and involving students in the evaluation process.The implementation of punishment to improve the good morals of fourth-grade students at SDN 15 Kartiasa includes: (1) Calling in and listening to the student's explanation regarding the situation that led to the mistake, (2) Choosing and administering punishment appropriate to the level of violation, such as having students who fought sit together, (3) Ensuring that the punishment is educational and helps students learn from their mistakes, such as helping students who are late to read the Qur'an, (4) Providing support and guidance to help students learn from their mistakes, with teachers assisting in reflecting on the errors.The evaluation of punishment in enhancing the good morals of fourth-grade students at SDN 15 Kartiasa includes: (1) Process evaluation by observing student behavior, (2) Self-evaluation by involving students to write about their punishment experiences, (3) Reflection with parents, where parents visit/contact teachers for consultation